Organic Waste Management Innovation through Composting Technology with Local Bio-Activators - Eka Putra Ramdhani; Hilfi Pardi; Nola Ritha (ALCHEMY Jurnal Penelitian Kimia, 2026)
This research is part of a strategic research program in environmental technology and renewable energy focused on climate change mitigation. Organic waste management through composting technology is a strategic approach to reduce waste generation and the potential for methane (CH₄) emissions from anaerobic decomposition. This study aimed to analyze the effectiveness of local microorganism (MOL) bioactivators, namely rice MOL (P1), banana mob MOL (P2), and fruit MOL (P3), in accelerating composting, compared to controls (without the addition of MOL). The results showed that fruit MOL (P3) is the most effective bioactivator for accelerating decomposition and improving compost quality. This treatment achieves the fastest maturity in 40 days with the lowest C/N ratio and the highest macronutrient content (Nitrogen (N), Phosphorus (P), Potassium (K)) compared to other treatments. These findings confirm that the application of local bioactivators can significantly improve the efficiency of campus organic waste management and support environmental sustainability.